Caracterización morfológica de hongos fitopatógenos en el cultivo de mora de castilla (rubus glaucus benth) sector Huachi Chico-Ambato-Tungurahua, 2014 - Banda Vichicela, Patricia Elizabeth (2014)
The present research of MORPHOLOGICAL CARACTERIZATION OF PHYTOPATHOGENIC FUNGI IN MORA DE CASTILLA CROPS Rubus Glaucus Benth IN THE HUACHI CHICO FIELD - AMBATO-TUNGURAHUA. 2014.Research conducted at the Technical University of Cotopaxi laboratory, located in the Eloy Alfaro parish, Latacunga city, and Cotopaxi province, the main aim was to determine the phytophatogenic fungus with greatest impact on crop production, information that allowed the development of the research determining that Botrytis cinérea is the main limiting factor in the production of mora de Castilla Rubus glaucus Benth, devaluating economically with 50 percent loss in the production and marketing fruit. It was taken samples field in mora de Castilla crops identifying signs and symptoms of Botrytis cinerea, which were transferred to the laboratory employing the harvest method papa-destroza-agar (PDA), means for evaluating the morphological appearance and widely used for the isolation of fungi, using plastic petri boxes, five isolations were performed using pieces of 3mm plant stalks leaves, flowers and fruits with the fungus Botrytis cinerea contained, achieving greater efficiency with the use of pieces of 3mm of fruit, are introduced into the incubator at 23 ° C….